2-((E)-{2-[(1E)-(2,4-Dihydroxybenzylidene)amino]phenyl}iminiomethyl)-5-hydroxyphenolate methanol solvate - Eltayeb, Naser Eltaher (International Union of Crystallography, 2008)
The asymmetric unit of the title compound, C(20)H(16)N(2)O(4)·CH(3)OH, contains two Schiff base zwitterions and two methanol solvent molecules. The dihedral angles between the central benzene ring and the two outer benzene rings of the Schiff base are 2.57 (7) and 52.30 (7)° in one molecule and 5.83 (7) and 49.82 (7)° in the other molecule. Intramolecular O—H⋯N and N—H⋯O hydrogen bonds generate S(6) ring motifs, whereas intramolecular N—H⋯N hydrogen bonds generate S(5) ring motifs. In the crystal structure, O—H⋯O, hydrogen bonds and weak C—H⋯O interactions link the molecules into one-dimensional chains along the b-axis direction and are further connected by O—H⋯O and weak C—H⋯O interactions into a three-dimensional network. C—H⋯π and π–π interactions [centroid–centroid distances = 3.6228 (9) and 3.6881 (9) Å] are also observed in the crystal structure.